A critical analysis of the tax consequences of debt reductons, in the context of insolvency, death and the liquidaton of a deceased estate - Simango, Samuel (Rhodes University, Faculty of Commerce, Department of Accounting, 2014)
The present research was conducted in an effort to address certain problems and a legal anomaly that is specifically related to the tax treatment of reduced debts stemming from the death or insolvency of natural persons in South Africa. At the beginning of 2013 the National Treasury enacted certain amendments to the debt reduction provisions of the Income Tax Act 58 of 1962 with the intention of streamlining the tax treatment of reduced debts and granting debt relief to financially distressed debtors. In spite of these recent amendments to the provisions of the Income Tax Act, there are certain problems and a legal anomaly which still currently relate to the tax consequences of reduced debts in South Africa. These problems and the legal anomaly are based on the failure of the recent amendments to successfully address debt reduction which arises in the context of the death and/or insolvency of natural persons. The objective of this research was therefore to analyse the tax consequences of reduced debts arising in the context of the death and the insolvency of natural persons and to explain how the problems and legal anomaly associated with these tax consequences can be rectified. The research design was qualitative within the framework of an interpretive paradigm. A mixed methodology approach was followed as identified in the Arthurs Report (1983), namely the interdisciplinary and the doctrinal methodologies. This approach encompassed two legal research methods namely the expository and legal reform research methods. The research explained the underlying nature of the tax consequences of reduced debts arising in the context of the death and the insolvency of natural persons and formulated specific reform measures aimed at remedying the problems and the legal anomaly that currently exist. Two amendments were proposed. It was proposed that the tax liability which arises when debts are reduced through the wills of deceased persons and the reduction of debts stemming from the insolvency of natural persons should be expressly excluded from falling within the ambit of the provisions which give rise to tax consequences whenever debt reduction takes place.
Keywords: Uncatalogued